Thematic Study of “Ayman al-ʿAtūm”’s Prison Novels - Muhammet Berat Can (Şarkiyat Mecmuası)
The novel is a prose genre whose origins are thought to be based on epics and whose first examples emerged in Europe. The development of the novel genre in Arab geography has experienced some difficulties. Some types of novels with unique styles were prevented from being distributed and published by various censors. The genre that calls itself prison literature deals with the life stories of prisoners in prison, their torture, and the hardships they experience. The general themes of these novels are freedom, exhaustion, despair, and resistance. Although works have been written in this genre in the West, this genre also has a special place in Arabic literature. Authors such as Abdurrahman Munif, Majid Suleiman, Mustafa Khalifa and Ayman al-ʿAtūm stand out in Arabic literature. Ayman al-ʿAtūm, whose novels feature an Islamist aspect, is one of the most important figures in modern Arabic literature. In both his novels Yā Sāhibeyi’s-Sijn and Yāsmeūne Hasīsehā, he experienced and fictionalized the punishment of rebelling against authority or holding different views in societies ruled by authoritarian regimes and in which democracy exists only in words. In addition to being an engineer, the author is an academic and a man of letters.